Effect of training on agility at high altitude in Border Collie dogs on some electrocardiographic variables: preliminary analysis - Vargas-Pinto, Piero (2018)
The aim of this study was to investigate the effect of the practice of the sport discipline of Agility at high altitude (2600 meters above sea level) on some electrocardiographic variables in Border Collie dogs at rest. Fifteen dogs (athlete group), belonging to different «Agility» teams from the city of Bogota D.C., Colombia and 16 Border Collie dogs, not trained in regular or athletic activities (non-athlete group) from the same city were evaluated. The electrocardiographic variables analyzed (5-min electrocardiography) were: spectral power density with high and low frequency components and LF/HF (sympathetic/vagal) balance. Within the time domain method, the mean RR (NN) and SDNN were determined. The duration of QRS and QT was corrected (QTc) and its variability by standard deviation (SDQT) was measured in 100 consecutive beats. Observation of the QT dispersion of each individual was performed by Poincaré plot. The athlete group showed higher values of HF and of LF, and LF/HF lower than the non-athlete group (p<0.05). The values of RR and SDNN, QRS length and QT interval were also higher in athlete dogs (p<0.05). No differences were found between the groups in QTcV and SDQT. The results showed differences in several components of the heart rate variability (HRV) between Border Collie athletes and non-athletes, with differentiated activity of the autonomic nervous system. Exercise and altitude would be responsible for QT and QRS findings.